Investigation of pozzolanic properties of acidic and basic tuffs: A case study from Elazığ and Gümüşhane regions - Aslan Topçuoğlu, Yasemin; Gürocak, Zülfü (Gumushane University, 2022)
Pozzolans are used as additives in stabilizing clayey soils and as trass in cement production. Natural and unnatural pozzolans added to the ground in the stabilization process increase the bearing strength and strength of the soil, reduce the deformations that will occur as a result of stresses, settlements, swelling potential, liquefaction potential and permeability. It Pozzolans, which are used in cement and called trass, reduce the heat of hydration, increase the resistance of concrete against cracking, increase the waterproofing of the concrete and prevent the expansion caused by the alkali-aggregate reaction. For this reason, researching materials with natural pozzolanic properties and examining their pozzolanic properties are important for the country's economy. In this study, chemical and mineralogical studies were carried out to determine the pozzolanic properties of acidic and basic tuffs, and pozzolanic activity tests were carried out on the tuffs. As a result of the studies, although the acidic character tuffs belonging to the Kızılkaya Formation meet the conditions for use as an additive in the stabilization and cement production recommended in the standards, they cannot provide sufficient compressive strength in the pozzolanic activity test. This is due to the low CaO ratio. For this reason, it is necessary to increase the CaO ratio with lime additives in the use of acidic tuffs. It has been concluded that the chemical properties of the basic character tuffs of the Karabakır Formation are not in accordance with the limit values given in the standards, they will not create sufficient pozzolanic reaction and cannot be used as an additive material. © 2022, Gumushane University. All rights reserved.
Asidik ve bazik karakterli tüflerin puzolanik özelliklerinin araştırılması: Elazığ ve Gümüşhane yörelerinden örnek bir çalışma
Keywords: Clay; Pozzolan; Stabilization; Trass; Tuff